AKUN INSTAGRAM SEKOLAH RELAWAN DAN PENGARUHNYA TERHADAP PEMBENTUKAN KEPEDULIAN SOSIAL DI KALANGAN GENERASI-Z - Edy Prihantoro; Dwi Asih Haryanti; Noviawan Rasyid Ohorella; Susilowati Dyah Kusumaningtyas (Metacommunication: Journal of Communication Studies, 2021)
Instagram @sekolahrelawan is an account that is a place for users to share and help others. This study aims to see the influence of the media on the Instagram account @sekolahrelawan Volunteers on the level of concern among Generation-Z. This research uses quantitative research with an explanatory approach. This research was conducted by sending online questionnaires to AKMRTV Jakarta students who are followers or have seen Instagram @sekolahrelawam content. Respondents in this study were 86 people and were determined based on simple random sampling. Meanwhile, to obtain data through a questionnaire or questionnaire. The results of this study indicate that the influence of Instagram @sekolahrelawan on the level of social care among generation z. Evidenced by the value of the regression coefficient in this study is Y = 39.261 + 0.618X. The constant number is 39,261 and the Instagram influence variable is 0.618. Meanwhile, t count 39.261 is bigger than t table 16.63, with a significance level of 0.000 smaller than α = 0.05. Based on the table "Model Summary", that the value of R = 0.618 and the coefficient of determination (Rsquare) is 0.464. This figure shows the understanding that the contribution of the @sekolah volunteer Instagram account attack variable to the Level of Social Care among Generation Z at AKMRTV Jakarta is 61.8%. The @Sekolahrelawan  account has a positive influence on Generation Z social care. The information conveyed through this account provides a clear picture of social realities in society that require the care of all parties, especially Generation Z.